2011
DOI: 10.1016/j.dza.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Brain encoding of acupuncture sensation – coupling on-line rating with fMRI

Abstract: Acupuncture-induced sensations have historically been associated with clinical efficacy. These sensations are atypical, arising from sub-dermal receptors, and their neural encoding is not well known. In this fMRI study, subjects were stimulated at acupoint PC-6, while rating sensation with a custom-built, MR-compatible potentiometer. Separate runs included real (ACUP) and sham (SHAM) acupuncture, the latter characterized by non-insertive, cutaneous stimulation. FMRI data analysis was guided by the on-line rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
1
28
1
1
Order By: Relevance
“…[237][238][239][240][241] Therefore, studies comparing acupuncture or dry needling with sham needling may actually compare two treatment regimens. 242 In some studies, sham needling is attempted by tapping a von Frey monofilament on the skin; 243 however, both the actual needling and the tapping can induce specific brain responses, which means that tapping is not a suitable sham procedure either. The observation that both needling and sham acupuncture caused specific changes emphasizes the importance of including control groups in studies.…”
Section: Dry Needling and Trigger Pointsmentioning
confidence: 99%
“…[237][238][239][240][241] Therefore, studies comparing acupuncture or dry needling with sham needling may actually compare two treatment regimens. 242 In some studies, sham needling is attempted by tapping a von Frey monofilament on the skin; 243 however, both the actual needling and the tapping can induce specific brain responses, which means that tapping is not a suitable sham procedure either. The observation that both needling and sham acupuncture caused specific changes emphasizes the importance of including control groups in studies.…”
Section: Dry Needling and Trigger Pointsmentioning
confidence: 99%
“…As a result, fMRI has been one of the most important tools to investigate acupuncture 1 efficacy in the last 20 years. [7][8][9] In most of these fMRI studies on acupuncture, a block design is used 10,11 in which consecutive acupuncture stimulations are given in order to detect neural responses.…”
Section: Introductionmentioning
confidence: 99%
“…25 It has been reported that SI processing is performed with input provided by mechanoreceptors, 26 but the activation of much of the SI has not been conˆrmed by acupuncture stimulation. 1,2,[4][5][6][7][8][10][11][12][13][14] The peripheral receptors involved in acupuncture stimulation have been suggested to be the polymodal receptors that are nociceptive receptors of the C-ˆbers. 27 It is also thought that the input is the transmission through C-ˆber in response to production of a chemical substance following deep tissue injury by manual acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, the development of imaging techniques, such as functional magnetic resonance imaging (fMRI), has opened the door for the study of brain activity in response to acupuncture stimulation. Numerous studies have been performed with fMRI and a variety of acupuncturerelated stimulations, such as electroacupuncture, 1,2 manual acupuncture, [1][2][3][4][5][6][7][8][9][10][11][12][13] sham acupuncture of the skin some distance from a known acupoint [4][5][6] or by noninsertive acupuncture and poking of the skin over an acupuncture point, [7][8][9][10][11] pressure to the acupoint, 12 laser acupuncture, 13 and electrical acupoint stimulation. 14 fMRI studies of acupuncture have typically utilized a block design that is used as a general linear model regressor in the analysis of fMRI data based on the assumption that mechanoreceptors and nociceptor-associated aŠerence work coincidentally with acupuncture stimulation, which is the conscious perception and evaluation of this aŠerence.…”
Section: Introductionmentioning
confidence: 99%